Education Management: Decision-Making Strategies in Technology Integration in The Digital Age - Teguh Trianung D.S; Winda Sundari; Andi Kurniawan; Nugraha Adhi Setiawan; Jihan Aisyah (AL-ISHLAH: Jurnal Pendidikan, 2024)
In an increasingly digitally connected environment, the right use of technology can open doors for innovation, collaboration, and improved results. However, to succeed in applying technology, informed decision-making is required. This study aims to explore decision-making strategies for technology integration in educational management during the digital era. The research employs a qualitative descriptive analysis approach, a method used to discover knowledge or research theory at a specific time. Primary data, collected directly from the source, is central to this case study. Focusing on "TechEd University," an institution known for its innovative educational approaches, the study examines the challenges of technology integration, including catering to diverse technological needs within limited resources. TechEd University's strategies include thorough needs assessments, active stakeholder involvement, reliance on data-driven insights, pilot projects, professional development opportunities, and flexible policies. The implementation process involves identifying technology needs, evaluating potential solutions, pilot testing, review, iteration, and continuous monitoring and evaluation. Data collection involved a comprehensive literature review and documentation analysis, revealing critical insights into education management and decision-making strategies. The results of this study show that overall, decision-making in technology integration is not just about technology adoption; It reflects strategic efforts to harness the potential of technological transformation to achieve significant results. By leveraging technology integration models, carefully evaluating technology needs, and implementing effective decision-making practices, educational organizations, and institutions can navigate the complexities of technology integration with confidence. As we embark on this journey, it is important to remember that effective decision-making is not just a goal but an ongoing journey of adaptation and innovation from an ever-evolving technological perspective.